Uterine Arteriovenous Fistula with Concomitant Pelvic Varicocele: Endovascular Embolization with Onyx-18® - Francesco Giurazza; Fabio Corvino; Andrea Paladini; Antonio Borzelli; Domenico Scognamiglio; Giulia Frauenfelder; Giuseppe Albano; Fabio Sirimarco; Raffaella Niola (Case Reports in Vascular Medicine)
Uterine arteriovenous fistulas are rare and acquired causes of life-threatening vaginal bleeding. They usually present with intermittent menometrorrhagia in young patients in childbearing age with history of gynecological procedures on uterus. Traditional management is hysterectomy; endovascular embolization represents nowadays an alternative strategy for patients wishing to preserve fertility. Here, the endovascular approach to a 29-year-old woman affected by severe menometrorrhagia caused by a uterine arteriovenous fistula with a concomitant pelvic varicocele is reported; a bilateral uterine arteries embolization with Onyx-18 (ev3, Irvine, CA, USA) has successfully resolved the fistula with clinical success.